Cobalt Distribution in Ultramafic Laterite Profiles: Integration of Morphology, Drilling Data, and Geochemistry, in North Konawe Regency - A. Okto; Hasria; A. A. W. Aqdi; I W. Sutapa (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2025)
The research location is located in the Wiwirano area, North Konawe Regency, Southeast Sulawesi Province. The stratigraphic arrangement is based on the regional geology of the Lasusua-Kendari sheet, the study site is dominated by the Ultramafic Complex with hilly morphology. This research was conducted by analyzing drilling data in the form of drilling logging descriptions and XRF geochemical analysis data in 11 drill holes with elements of Ni, Fe, Co, and Mn which aims to determine the presence of cobalt in the laterite profile which is visualized in the form of drill hole logs and variations in nickel thickness. Elevation and type of topography affect the cobalt content contained where the highest cobalt content is at an altitude of 437 meters above sea level (hills) with rather steep slopes. The bedrock that composes the study area consists of dunit where olivine is the main Co element carrier associated with geothite and manganese elements. The element cobalt is richest in the top soil zone to the limonite zone and the element cobalt in the study area also has a strong positive relationship with the elements MnO, Cr2O3 and Fe. The element of cobalt in the study area increased with the presence of geothite and manganese wood minerals and was inversely proportional to the presence of silica minerals.